Temoporfin-loaded 1-tetradecanol-based thermoresponsive solid lipid nanoparticles for photodynamic therapy - Brezaniova, Ingrid; Hruby, Martin; Kralova, Jarmila; Kral, Vladimir; Cernochova, Zulfiya; Cernoch, Peter; Slouf, Miroslav; Kredatusova, Jana; Stepanek, Petr (Journal of controlled release, 2016)
We developed fully biodegradable/metabolizable nanosystem based on polymer surfactant-stabilized thermoresponsive solid lipid nanoparticles with non-covalently bound photosensitizer temoporfin (T-SLNP) with particle size below 50nm. The efficacy of T-SLNP was compared with commercial temoporfin formulation in terms of in vitro phototoxicity in 4T1 (murine mammary carcinoma) and MDA-MB-231(human breast adenocarcinoma) cells and of in vivo anticancer effect in Nu/Nu mice bearing MDA-MB-231 tumors. In vitro study demonstrated faster accumulation kinetics in the cells for our formulation design resulting in higher phototoxicity against the tumor cells. In vivo anticancer efficacy was markedly improved by T-SLNP compared with commercial temoporfin formulation. Owing to controlled and sustained release properties, subcellular size, biocompatibility with tissue and cells, the T-SLNP nanodispersion prepared in this study represents promising drug delivery system applicable in cancer treatment.
Keywords: Animals; Nanomedicine; mastné alkoholy; Female; Cell Line, Tumor; Photodynamic therapy; ženské pohlaví; Mice, Nude; Nanoparticles; lipidy; Drug Carriers; lidé; Mammary Neoplasms, Experimental; Photochemotherapy; Mice; Photosensitizing Agents; Lipids; nanočástice; myši; Drug delivery; fotosenzibilizující látky; Humans; mesoporfyriny; Mesoporphyrins; nosiče léků; Fatty Alcohols; zvířata; Temoporfin; fotochemoterapie; myši nahé; nádorové buněčné linie; Solid lipid nanoparticles; experimentální nádory mléčných žláz